The effect of whole body vibration on the dynamic stability of women basketball players - Ebben, W.; Petushek, E.; Nelp, A. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study investigated the effect whole body vibration (WBV) on the dynamic stability of NCAA Division I women basketball players. Eleven subjects were evaluated in two test conditions including one with and one without WBV. After each condition, subjects were tested for time to stabilization (TTS) on a force platform during bilateral, right leg, and left leg countermovement jumps (CMJ). Results of the statistical analysis revealed no significant difference in TTS between the vibration and non-vibration conditions for the bilateral (p = 0.24) and right leg (p = 0.48) CMJ. A significant difference was found between the conditions demonstrating a shorter TTS in the non-vibration condition for the left leg CMJ (p = 0.04, d = 0.57, ?p² = 0.36). Acute WBV has no effect on and in some cases impairs dynamic.